Experimental and numerical studies on flow from axisymmetric nozzle flow with sudden expansion for mach 3.0 using CFD. - Quadros, Jaimon Dennis; Khan, Sher Afghan; Antony, A J; S.Vas, Jolene (NOVA Science Publishers, 2016)
Researches over late in the field of aerodynamic vehicles have been concerned with the problem of flow separation over its base which has led to the establishment of low pressure circulation region. This pressure is found to be noticeably lower in comparison with the free stream atmospheric pressure. Base drag due to such pressure differences can be up to two-thirds of the total drag which is primarily dictated by base pressure. The present study aims to conduct experiments in order to study the base pressure variation from an axisymmetric nozzle exit of 10 mm diameter. Area ratio i.e., ratio of area of duct which is suddenly expanded to nozzle exit area considered in this particular study is 4.84. The fundamental control parameters considered in the current study are the nozzle pressure ratio (NPR) and length-to-diameter (L/D) ratio which apparently are termed to be inertial and geometric parameters respectively. The tests have been conducted for NPR’s spanning from 3 to 11 in steps of 2. Accordingly L/D ratio was varied from 10 to 1 where tests were conducted for L/D ratios of 10, 9, 8, 7, 6, 5, 4, 3, 2 and 1. The results revealed that for increase in the NPR values once the flow is attached to the duct, the base pressure steadily decreased. Wall pressure distribution throughout the enlarged duct has also been studied in order to understand the oscillatory flow nature. The present work also proposes an effective numerical model for base pressure by use of Computational Fluid Dynamics (CFD). The numerical model of the axisymmetric nozzle and the enlarged duct was designed using ANSYS Fluent which is the CFD solver and engaged in the present work. Numerical iterations were completed, and specific values for base pressure have been analyzed. The numerical results were found to be in good agreement with the experimental ones.